Improving postharvest handling of the Royal Project vegetables - P. Poonlarp (2018)
© 2018 International Society for Horticultural Science. All rights reserved. The Royal Project Foundation has underlined the importance of the Research and Development in farming vegetables and herbs from the very beginning stage until the products were delivered to end customers. The Royal Project produces were Good Agricultural Practices (GAP) and Good Manufacturing Practice (GMP) certified, which represents safety in the entire food chains from farms through end consumers. This has significantly increased products’ capacity to compete both domestically and internationally. Appropriate postharvest management to reduce losses of vegetables in the Royal Project Foundation was conducted by surveying and gathering information on supply chain of five vegetables, namely broccoli, spinach, head lettuce, cabbage and Chinese cabbages. Postharvest losses of vegetables were determined at each stage of the supply chain starting from Chiang Mai province through Bangkok; in the field after harvesting, at the Development Center packinghouse, at Chiang Mai packinghouse, at Bangkok packing house and at the Royal Project retail shop in Bangkok. The results showed that broccoli, spinach and head lettuce postharvest losses were 71.89, 58.66 and 51.32%, respectively. The main factor contributing to losses of broccoli was due to mechanical damage and underutilized parts and/or short of minimum quality standard. Postharvest losses of cabbage and Chinese cabbage were 38.64 and 32.75%, respectively. After applying appropriate postharvest management, for example, temperature control, hygienic cleaning, using active packaging and reducing the duration of the supply chain, postharvest losses of all vegetables were remarkably reduced.